2005
DOI: 10.1029/2005gl022526
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Arctic Oscillation pattern on interannual forest fire variability in Central Siberia

Abstract: Russia's forests play an important role in the global carbon cycle. Because of their scale and interannual variability, forest fires can change the direction of the net carbon flux over Eurasia. 2002 and 2003 were the first two consecutive years in the atmospheric record in which the carbon content rose by more than 2 ppm per year. Northern Hemisphere fires could be the reason. We show that 2002 and 2003 were the two years with the largest fire extent in Central Siberia since 1996 using new measurements of bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 20 publications
4
83
0
Order By: Relevance
“…The fire return interval has a substantial direct effect on biomass. In 2003, 43.3 TgC were consumed by fire in the SIBERIA-II study region based on the GIS analysis by the IIASA using burned area estimates from [Balzter et al, 2005]. The improved LPJ-DGVM independently agrees with 42.8 TgC.…”
Section: Model Evaluationsupporting
confidence: 53%
See 1 more Smart Citation
“…The fire return interval has a substantial direct effect on biomass. In 2003, 43.3 TgC were consumed by fire in the SIBERIA-II study region based on the GIS analysis by the IIASA using burned area estimates from [Balzter et al, 2005]. The improved LPJ-DGVM independently agrees with 42.8 TgC.…”
Section: Model Evaluationsupporting
confidence: 53%
“…The fire model embedded in the LPJ-DGVM [Thonicke et al, 2001] uses a statistical approach that does not resolve the interannual variability of fire occurrence, but the simulation of soil moisture taking into account freeze-thaw effects leads to a correct prediction of the mean fire probability (see auxiliary material). In the SIBERIA-II evaluation region, on average 1.2 Mha burned annually from 1992 to 2003 as derived from satellite data [Balzter et al, 2005]. The enhanced LPJ-DGVM calculates 1.5 Mha.…”
Section: Model Evaluationmentioning
confidence: 99%
“…Using measurements of burned forest area in Central Siberia (approx. 79-119 • E, 51-78 • N), Balzter et al (2005) showed that 2002 and 2003 were the two years with the largest fire extent in Central Siberia since 1996. This is the region within our Biomass Burning (BB) East map.…”
Section: Inversion Resultsmentioning
confidence: 99%
“…Observations from Indonesia show that fires in drained peatlands were a dominant source of emissions from this region during the 1997-1998 El Niño (Page et al, 2002). Interannual variability (IAV) in boreal fire activity is also large (Amiro et al, 2001;Sukhinin et al, 2004) and may be linked with the Arctic Oscillation (Balzter et al, 2005), ENSO (Hess et al, 2001), temperature anomalies (Balzter et al, 2005;Flannigan et al, 2005), and with human activity (Mollicone et al, 2006). At a global scale, two studies have assessed interannual variability in biomass burning emissions on a global scale using satellite data (Duncan et al, 2003;.…”
Section: G R Van Der Werf Et Al: Interannual Variability In Globalmentioning
confidence: 99%